العمق المالي ركيزة أساسية لتطوير الجهاز المصرفي في العراق للمده (2004 – 2020) - عويش حسين علي; مهيجر جابر حسن (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The concept of financial depth is one of the modern financial concepts to demonstrate the importance of the financial sector in achieving credit and providing lending and borrowing to gain public confidence in order to achieve monetary stability. This study aims to analyze the reality of financial depth in Iraq and ways to achieve monetary stability for the period (2003-2018), To reflect the degree of financial depth and the strength of the financial sector and its ability to grant loans and cash credit and take deposits, and thus the financial sector becomes influential and positively in achieving monetary stability, To reflect the degree of financial depth and the strength of the financial sector and its ability to grant loans, cash credit and take deposits, and thus the financial sector becomes influential and positive in achieving monetary stability. Activate the economy, and thus achieving monetary stability, not this, but rather that many economies have raised their economic growth rates as a result of the development of their financial activities and the possibility of mobilizing domestic savings to serve investment and how to withdraw and attract savings in order to enhance financial depth and raise rates of economic growth.